MODEL PEMBELAJARAN PJOK BERBASIS PERMAINAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA: STUDI KUASI-EKSPERIMEN - Nurudin, Amad; Wibowo, Sapto; Pudjijuniarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the impact of a game-based learning model on student learning motivation in Physical Education, Sports, and Health (PJOK) classes. Traditional PJOK teaching methods often feel monotonous, potentially leading to reduced student engagement and a loss of interest; therefore, a more interactive and enjoyable approach is needed. This study employed a quantitative approach using a quasi-experimental pretest-posttest control group design involving 56 fifth-grade elementary school students, divided into experimental and control groups. The instrument used was a learning motivation questionnaire with a validity of 0.82 and a reliability of 0.90. Data were analyzed using descriptive statistics and the Mann-Whitney test. The results indicate a significant increase in learning motivation in the experimental group compared to the control group, as evidenced by posttest scores (U = 5.000; Z = -6.399; p < 0.05). These findings suggest that the game-based physical education model helps enhance student engagement, enthusiasm, and active participation. This model is recommended as a new teaching strategy for elementary schools.